Proceedings of the Sixth International Conference on Tangible, Embedded and Embodied Interaction 2012
DOI: 10.1145/2148131.2148163
|View full text |Cite
|
Sign up to set email alerts
|

Exploring tabletops as an effective tool to foster creativity traits

Abstract: Creativity is a relevant characteristic for people's development as it facilitates the generation of new ideas and innovation processes. Although technology has played an important role on creativity stimulation, it still needs to be explored for a better understanding and support in the context of information and communication technologies. In this paper a basic creativity assessment model is presented and an empirical study has been conducted whose aim is to get insight into whether an interactive surface as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 20 publications
1
21
0
Order By: Relevance
“…Other studies (Sluis et al, 2004) (Khandelwal & Mazalek, 2007) and (Tyng et al, 2011) have shown that this technology can be used by children between three and seven to learn to read, solve mathematical problems, develop a sense of space, etc. Other studies have demonstrated that the technology can also be used to promote collaboration between peers (Rick & Rogers, 2008) (Rick et al, 2010) (González et al, 2001) and to foster creativity (Helmes et al, 2009) (Catala et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies (Sluis et al, 2004) (Khandelwal & Mazalek, 2007) and (Tyng et al, 2011) have shown that this technology can be used by children between three and seven to learn to read, solve mathematical problems, develop a sense of space, etc. Other studies have demonstrated that the technology can also be used to promote collaboration between peers (Rick & Rogers, 2008) (Rick et al, 2010) (González et al, 2001) and to foster creativity (Helmes et al, 2009) (Catala et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some studies have demonstrated that the technology can also be used to promote collaboration between peers [16,17,7] and to foster creativity [8,2].…”
Section: Related Workmentioning
confidence: 99%
“…This has been chosen to elicit both the Discovery and Expression pleasures, following also the concept that a too easy game bores the players [3]. In order to foster additional creativity OHR was designed to use a custom-built tangible interface [1].…”
Section: Gameplaymentioning
confidence: 99%